Candide a comic operetta in two acts - Bernstein, Leonard 1918-1990 (Kultur, 2009)
Leonard Bernstein's comic operetta is based on the classic Voltaire tale of an innocent young man's journey through a life filled with colorful characters and unexpected life lessons.
Interpr. u.a.: Robert Orth (Bar). Michael Slattery (Ten). Coro Lirico Aramus. Osvaldo Guidotti (Choreinstud.). Orchestra Sinfonica Nazionale di Malta. Jon de Main (Dir.). Enrico Castiglione (Regie). - Aufn.: Rom, Teatro Argentina, [2003]
Keywords: Geschichte 1700-1800; Conduct of life -- Drama; Enlightenment -- 18th century -- Drama; Operas; Optimism -- Drama; DVD-Video; Feature films; Fiction films; Filmed operas; Musical films